Divergent Metabolic Regulation of Autophagy and mTORC1—Early Events in Alzheimer’s Disease? - Shafei, Mai A.; Harris, Matthew; Conway, Myra E. (Frontiers in Aging Neuroscience, 2017)
Alzheimer’s disease (AD) is a progressive disease associated with the production and deposition of amyloid β-peptide (Aβ) aggregates and neurofibrillary tangles, which lead to synaptic and neuronal damage. Reduced autophagic flux has been widely associated with the accumulation of autophagic vacuoles, which has been proposed to contribute to aggregate build-up observed in AD. As such, targeting autophagy regulation has received wide review, where an understanding as to how this mechanism can be controlled will be important to neuronal health. The mammalian target of rapamycin (mTOR), which was found to be hyperactive in AD brain, regulates autophagy and is considered to be mechanistically important to aberrant autophagy in AD. Hormones and nutrients such as insulin and leucine, respectively, positively regulate mTOR activation and are largely considered to inhibit autophagy. However, in AD brain there is a dysregulation of nutrient metabolism, linked to insulin resistance, where a role for insulin treatment to improve cognition has been proposed. Recent studies have highlighted that mitochondrial proteins such as glutamate dehydrogenase and the human branched chain aminotransferase (hBCAT) protein, through metabolism of leucine and glutamate, differentially regulate mTOR and autophagy. As the levels of the hBCAT proteins are significantly increased in AD brain relative to aged-matched controls, we discuss how these metabolic pathways offer new potential therapeutic targets. In this review, we highlight the core regulation of autophagy through mTOR, focusing on how insulin and leucine will be important to consider in particular with respect to our understanding of nutrient load and AD pathogenesis.